Electrophysiological characteristics of feeding-related neurons after taste avoidance Pavlovian conditioning in Lymnaea stagnalis - Sunada, Hiroshi (Biophysics (Nagoya-shi), 2014)
Taste avoidance conditioning (TAC) was carried out on the pond snail, Lymnaea stagnalis. The conditional stimulus (CS) was sucrose which elicits feeding behavior; while the unconditional stimulus (US) was a tactile stimulus to the head which causes feeding to be suppressed. The neuronal circuit that drives feeding behavior in Lymnaea is well worked out. We therefore compared the physiological characteristics on 3 classes of neurons involved with feeding behavior especially in response to the CS in conditioned vs. control snails. The cerebral giant cell (CGC) modulates feeding behavior, N1 medial neuron (N1M) is one of the central pattern generator neurons that organizes feeding behavior, while B3 is a motor neuron active during the rasp phase of feeding. We found the resting membrane potential in CGC was hyperpolarized significantly in conditioned snails but impulse activity remained the same between conditioned vs. control snails. There was, however, a significant increase in spontaneous activity and a significant depolarization of N1M’s resting membrane potential in conditioned snails. These changes in N1M activity as a result of training are thought to be due to withdrawal interneuron RPeD11 altering the activity of the CGCs. Finally, in B3 there was: 1) a significant decrease in the amplitude and the frequency of the post-synaptic potentials; 2) a significant hyperpolarization of resting membrane potential in conditioned snails; and 3) a disappearance of bursting activity typically initiated by the CS. These neuronal modifications are consistent with the behavioral phenotype elicited by the CS following conditioning.